Economic Policy Uncertainty and consumer sentiment: Insights from different age demographics - Kallio, Akseli (2024)
This study investigates the influence of Economic Policy Uncertainty (EPU) and four other macroeconomic variables on consumer sentiment across three different age groups in the United States from 1985 to 2023. The study is conducted by using a Vector Autoregression (VAR) model and Granger causality test. The research explores the dynamics between EPU, Industrial Production Index, Consumer Price Index, and unemployment rate and their effects on consumer sentiment among three age groups, 18-34, 35-54, and 55+. The dynamics between variables are examined as a group and individually.